An unusual case of a solitary cardiac myofibroma causing severe right ventricular outflow tract obstruction in an infant. (26th February 2021) - Minocha, Prashant K.; Chen, Fei; Maleszewski, Joseph J.; Ludomirsky, Achiau; Mosca, Ralph; Kumar, T. K. Susheel
Abstract: Cardiac tumours are relatively uncommon, particularly in children. Myofibroma is an extremely rare variety of cardiac tumour, which nearly always arises in the context of infantile myofibromatosis. Herein, we present a case of a solitary cardiac myofibroma causing right ventricular outflow tract obstruction in a 2-month-old male infant.